Successful Aging-the Case for Prosthetic Therapy - Ejvind Budtz-Jsrgensen, DrOdont; Jean-Pierre Chung, DMD; Philippe Mojon, PhD (Blackwell Synergy, 2000)
Reduced chewing ability in community-dwelling older people is linked to the presence of removable dentures and having fewer than 20 natural teeth present. Compensation is provided by chewing longerand swallowing larger foodparticles. Replacement of posterior tooth loss by fixed or removable prostheses increases the activity ofthe masticatory muscles, and reduces chewing time and the number of chewing strokes until swallowing